1) 94 * 21 = ( 90 + 4 ) * ( 20 + 1 ) = 90 * 20 + 90 * 1 + 20 * 4 + 4 * 1 = 1800 + 90 + 800 + 4 = 2600 + 94 = 2694 47 * 2 * 21 = ( 47 * 2 ) * 21 = 94 * 21 = 2694так как первое выражение 94 * 21 = 2694 , то второе тоже также равно 2)86 * 14 = ( 80 + 6 ) * ( 10 + 4) = 80 * 10 + 80 * 4 + 6 * 10 + 6 *4 = 800 + 320 + 60 + 24 = 1120 + 386 = 1400 + 106 = 1506 86 * 7 * 2= 86 * ( 7 * 2 ) = 86 * 14 = 15063)76 * 38 = (70 + 6 ) * ( 30 + 8) = 70 * 30 + 70 * 8 + 6 * 30 + 6 * 8 = 2100 + 560 + 180 + 48 = 2600 + 60 + 180 + 48 = 2700 + 8 + 180 = 2800 + 88 = 288838 * 76= 76 * 38 = 2888